2009
DOI: 10.1053/j.ajkd.2008.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Antibody Response to Influenza Vaccination in Kidney Transplant Recipients: A Prospective Cohort Study

Abstract: Background Antibody response to the inactivated influenza vaccine is not well described in kidney transplant recipients on newer, but commonly used, immunosuppression medications. We hypothesized that kidney transplant recipient participants on tacrolimus-based regimens would have decreased antibody response compared with healthy controls. Study Design Prospective cohort study of 53 kidney transplant recipient and 106 healthy control participants over the 2006–2007 influenza season. All participants received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 30 publications
6
84
1
Order By: Relevance
“…Conversely, a series of 51 liver transplant recipients found vaccine responses corresponded with the length of time after transplant with H1 strain responses of 1/7 (14%) within 4 months of transplant, 6/9 (67%) within 4-12 months, and 30/35 (86%) within 12 months posttransplant; overall, more than 55% of the subjects vaccinated 4-12 months posttransplantation had adequate seroconversion to the three strains of the influenza vaccine (31). This was confirmed by a more recent study that showed significantly lower antibody titers in kidney transplant recipients vaccinated within 6 months of transplantation when compared to healthy controls (29). However, responses were similar to healthy controls if transplant patients were vaccinated after six months.…”
Section: Timing Of Influenza Vaccinationsupporting
confidence: 61%
“…Conversely, a series of 51 liver transplant recipients found vaccine responses corresponded with the length of time after transplant with H1 strain responses of 1/7 (14%) within 4 months of transplant, 6/9 (67%) within 4-12 months, and 30/35 (86%) within 12 months posttransplant; overall, more than 55% of the subjects vaccinated 4-12 months posttransplantation had adequate seroconversion to the three strains of the influenza vaccine (31). This was confirmed by a more recent study that showed significantly lower antibody titers in kidney transplant recipients vaccinated within 6 months of transplantation when compared to healthy controls (29). However, responses were similar to healthy controls if transplant patients were vaccinated after six months.…”
Section: Timing Of Influenza Vaccinationsupporting
confidence: 61%
“…The hemagglutination inhibition (HI) assay correlates with vaccine protection in immunocompetent patients, but it remains unclear whether the HI assay can predict protection against influenza in patients receiving immunosuppressive drugs, such as in SOT recipients [10][11][12]. Cell-mediated immunity appears to be a promising predictor of vaccine response [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Immunosuppression is most potent in the first year of transplant, and it is currently unknown whether or not immunization in the first year after transplantation is effective in preventing influenza infections or reducing their severity. There is literature to suggest that the influenza vaccine may not be effective after renal transplant on the basis of the inability to form seroprotective levels of antibodies (4,5).…”
Section: Introductionmentioning
confidence: 99%